Analysing the narrative and promises of 'avoided deforestation' implementation in Central Africa - Tsayem Demaze, M.; Sufo-Kankeu, R.; Sonwa, D.J. (Commonwealth Forestry Association, 2020)
Projects aimed at reducing emissions from deforestation and forest degradation (REDD+) have expanded in Central Africa following carbon certification standards, which were intended to demonstrate the feasibility of payments and rewards earned depending on a measured quantity of avoided deforestation. We used storytelling as a communication concept to analyse the narratives of five main certification standards that accompanied the implementation of REDD+ projects in Central Africa. Our analysis focuses on two storylines: the measurement of avoided deforestation, and payments or rewards. The examination of official documents disseminated by certification standards and the results from a survey of REDD+ stakeholders highlighted a gap between these promises and reality. Our findings show that carbon standards have diffused an idyllic view of REDD+, simplifying methods of measuring avoided deforestation and promising payments, co-benefits and sustainable development. Unkept promises result in disappointment and declining enthusiasm on the part of those involved in REDD+ projects at an early stage.